A systematic review of structures, and geometries of the thermoelectric generators. Issue 2 (31st October 2022) - Jaldurgam, Farheen F.; Ahmad, Zubair
Abstract: This systematic review presents the experimental and numerical optimization of the structure, design, and geometry of thermoelectric generators (TEGs). The critical aspect of this study is to evaluate the structures of different TEG designs in terms of their electric and thermal equivalent models. Thermal stress, contact resistance, heat pipe, and pulsed heating and cooling optimization have been judgmentally reviewed. This article will serve as a valuable and indispensable source of information on all aspects of thermoelectric design, structure, and geometry optimization. Abstract : The systematic review of different types of thermoelectric generator (TEG) structures and geometries was accomplished using PRISMA transparent reporting of systematic reviews and meta‐analysis guidelines. The outlook of article addresses the advantages and disadvantages of the geometries and structures. Additionally, it directs toward the path of future TEG research.